BAS/BSCR52 Investigating the importance of heparan sulphate in determining endothelial progenitor cell function. Issue 17 (26th August 2010) - Williamson, K; Haque, S; Bruce, I N; Stringer, S E; Alexander, M Y
Abstract : The increased risk of cardiovascular disease with age may, in part, be due to a decline in the function of endothelial progenitor cells (EPCs). Cell surface heparan sulphate proteoglycans (HSPGs) can bind a plethora of factors that are essential for EPC function. However, these interactions are dependent upon specific structures of HS. We aim to establish whether structural changes of HS on EPCs underlie the age-associated functional deterioration of these cells. The number and function of EPCs in patients with systemic lupus erythematosus (SLE), a disease associated with accelerated vascular ageing, was compared with age-matched healthy controls (52 patients and 30 controls; mean age 52 and 50 years, respectively). To enumerate EPCs, mononuclear cells were labelled with CD133 and CD34 and analysed by flow cytometry. The formation of colony-forming units (CFUs) after 7 days in culture was a measure of EPC function. Cell surface HS structure was analysed using high performance liquid chromatography. While EPC levels did not significantly differ, impairment in EPC function with vascular ageing was evident from the significantly reduced mean number of CFU (7 (SD=5) vs 17 (SD=18), p=0.01), with fewer large CFU (17% vs 40%; p<0.05) in patients than in controls. Preliminary data suggest decreased 2-O-sulphation of HS in association with vascular age. Ongoing studies are investigating if this affects EPC migration, proliferation and integration into vascular structures. Proving our hypothesis will improve our understanding of age-associated endothelial dysfunction and ascertain whether EPCs and/or HS oligosaccharides have therapeutic potential to attenuate age-associated vascular pathologies.